AB0582 Effect of Vitamin D Deficiency and Replacement on Endothelial Functions in Familial Mediterrenean Fever. (10th June 2014) - Can, M.; Eren, R.; Baykan, O.; Asmaz-Haliloglu, O.; Gogas-Yavuz, D.; Haklar, G.; Direskeneli, H.
Abstract : Background: Although patients with familial Mediterranean fever (FMF) are symptom-free between the attacks, subclinical inflammation may continue. Vitamin D (vit D) plays an important role in the modulation of immune system and might also influence the course of FMF. Endothelial dysfunction is previously demonstrated in Behcet's disease (BD) and vit D is implicated to modulate endothelial functions. Objectives: We aimed to evaluate the status of serum 25(OH)Vit D3 levels and its association with disease activity, endothelial function and carotis intima media thickness (CIMT) in patients with FMF. Methods: Sixty-two FMF (F/M: 42/20, mean age: 33.5 years), 43 ankylosing spondylitis (AS) (F/M: 19/24, mean age: 40.9 years) patients and 46 healthy controls (HC) (F/M: 26/20, mean age: 34.7 years) were studied. Serum 25(OH)Vit D3 levels were measured by HPLC method. Endothelial function was evaluated by brachial artery flow mediated dilatation (FMD) and CIMT with B-Mode ultrasound. The vitamin D-deficient BD patients received 1000 IU Vitamin D3 daily for 3 months. At the end of the third month of treatment, the subjects were re-evaluated for the same parameters (CIMT and FMD). Results: The mean (SD) disease duration was 8.2 (7.8) vs 8.4 (6.5) years (p>0.05) in FMF and AS patients, respectively. All FMF patients were on attack-free period and all of them were on colchicine treatment. A significant difference was observed between the levels of 25(OH)Vit D3 between the groups [median (range): 11.3 (2.7-48.3), 12.7 (4-37) and 56 (14-125), FMF, AS and HC, respectively), p=0, 001]. CIMT and FMD measurements were similar between groups (p>0.05). Serum 25(OH)Vit D3 levels were not observed to correlate with CIMT or FMD measurements. A significant increase of 25(OH)VitD3 levels after replacement therapy [11.3 (2.7-48.3), vs 30 (13-72) p=0.001] was observed after 3 months of therapy. Also, after replacement therapy, CIMT measurements improved (1, 04 vs 0.50, p=0.001) and FMD measurements improved (4, 9 vs 10, 2, p=0.01) Conclusions: A high presence of Vitamin D deficiency was observed in FMF patients from Turkey. Although impaired vascular endothelial function did not correlate with vitamin D levels, vitamin D deficiency may influence the course of the attacks and be related to some colchicine-resistant cases. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5994